Power electronics technologies for renewable energy sources - Coelho, Sergio (2022)
Over the last decades, power grids are facing significant improvements mainly due to the integration of more and more technologies. In particular, renewable energy sources (RES) are contributing to moving from centralized energy production to a new paradigm of distributed energy production. Analyzing in more detail the requirements of the diverse technologies of RES, it is possible to identify a common and key point: power electronics. In fact, power electronics is the key technology to embrace the RES technologies towards controllability and the success of sustainability of power grids. In this context, this book chapter is focused on the analysis of diverse RES technologies from the point of view of power electronics, including the introduction and explanation of the operating principle of the most relevant RES, both in onshore and offshore scenarios. Additionally, are also presented the main topologies of power electronics converters used in the interface of RES.